Anodal transcranial direct current stimulation of parietal cortex enhances action naming in Corticobasal Syndrome - Manenti, Rosa; Bianchi, Marta; Cosseddu, Maura; Brambilla, Michela; Rizzetti, Cristina; Padovani, Alessandro; Borroni, Barbara; Cotelli, Maria (Frontiers in Aging Neuroscience, 2015)
Background: Corticobasal Syndrome (CBS) is a neurodegenerative disorder that overlaps both clinically and neuropathologically with Frontotemporal dementia (FTD) and is characterized by apraxia, alien limb phenomena, cortical sensory loss, cognitive impairment, behavioral changes and aphasia. It has been recently demonstrated that transcranial direct current stimulation (tDCS) improves naming in healthy subjects and in subjects with language deficits. Objective: The aim of the present study was to explore the extent to which anodal tDCS over the parietal cortex (PARC) could facilitate naming performance in CBS subjects. Methods: Anodal tDCS was applied to the left and right PARC during object and action naming in seventeen patients with a diagnosis of possible CBS. Participants underwent two sessions of anodal tDCS (left and right) and one session of placebo tDCS. Vocal responses were recorded and analyzed for accuracy and vocal Reaction Times (vRTs). Results: A shortening of naming latency for actions was observed only after active anodal stimulation over the left PARC, as compared to placebo and right stimulations. No effects have been reported for accuracy. Conclusions: Our preliminary finding demonstrated that tDCS decreased vocal reaction time during action naming in a sample of patients with CBS. A possible explanation of our results is that anodal tDCS over the left PARC effects the brain network implicated in action observation and representation. Further studies, based on larger patient samples, should be conducted to investigate the usefulness of tDCS as an additional treatment of linguistic deficits in CBS patients.